2018
DOI: 10.5897/jpbcs2018.0750
|View full text |Cite
|
Sign up to set email alerts
|

Inheritance and combing ability in maize using a 7x7 diallel cross

Abstract: Twenty one F1s produced from 77 diallel mating along with the 7 parents were evaluated to notice the inheritance and combining ability of different traits to obtain high heterotic crosses. Genetic analysis and combing ability were analyzed following Hayman's and Griffing's diallel analyses, respectively. Hybrids projecting positive or negative potency ratio with >1.0 value for those traits is also the sign of incidence of over-dominance in desirable direction, and heterosis breeding is important to improve th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 21 publications
2
5
0
Order By: Relevance
“…For days to 50% silking minimum heterosis was shown by NCEV-4 × NCEV-1530-11 (-2.08%) and NCEV-4 × EV-70040 (-1.58%). Similar heterosis for days to 50% pollen shed was reported earlier in maize by Karim et al (2018) and Begum et al (2018).…”
Section: Days To 50% Silkingsupporting
confidence: 88%
See 1 more Smart Citation
“…For days to 50% silking minimum heterosis was shown by NCEV-4 × NCEV-1530-11 (-2.08%) and NCEV-4 × EV-70040 (-1.58%). Similar heterosis for days to 50% pollen shed was reported earlier in maize by Karim et al (2018) and Begum et al (2018).…”
Section: Days To 50% Silkingsupporting
confidence: 88%
“…These crosses showed better plant height than their parents. Karim et al (2018) and Begum et al (2018) also obtained similar results and observed significant positive levels of mid-parent heterosis for plant height in their studies.…”
Section: Plant Heightsupporting
confidence: 61%
“…P1×P2, P1×P4, P4×P5, and P6×P7 showed significant negative SCA effects for plant height indicating the better specific combinations of these hybrids for plant height, which is desirable as short-statured plants are mostly lodging tolerant. But Begum et al, (2018) found no significant and negative SCA effects for plant height. Considering yield, seven crosses performed significant and positive SCA effects for grain yield (Table 04) and most of them also possessed high mean values for the trait (Table 01).…”
Section: Specific Combining Ability (Sca) Effectsmentioning
confidence: 79%
“…The percent heterosis for grain yield varied from -85.76 to 10.83% (Table 05). Moreover, Karim et al, (2018), Talukder et al, (2016) and Begum et al, (2018) found 5.25%, 12.53 % and 9.9% significant positive heterosis in their studied materials, respectively. Among the 28 F1, three crosses revealed positive heterosis for grain yield.…”
mentioning
confidence: 79%
See 1 more Smart Citation